Coloration, Paternity, and Assortative Mating in Western Bluebirds. (14th October 2014) - Jacobs, Anne C.; Fair, Jeanne M.; Zuk, Marlene; Ebensperger, L.
Abstract Coloration in birds can act as an important sexual signal in males, yet in many species, both sexes display bright colors. Social selection may account for this pattern, with more brightly colored individuals pairing together on the best territories. Mutual mate choice may also explain this, as males investing a great deal of parental care in the offspring should be choosy about their social mates. It is less clear whether this pattern of mate choice can apply to extra‐pair partners as well. We examined western bluebirds (Sialia mexicana) to determine whether more colorful individuals tended to pair with one another, both in social pairs and between females and their extra‐pair partners. Both male and female western bluebirds display both UV‐blue structural plumage and a melanin‐based chestnut breast patch, although females are duller than males. Social pairs mated assortatively with regard to UV‐blue brightness, but not chestnut coloration. There was no evidence that extra‐pair partners mated assortatively, but males with brighter UV‐blue coloration had fewer extra‐pair offspring in their nests. Older males were more successful at siring extra‐pair offspring, despite displaying no differences in coloration compared to younger males. Coloration did not play a role in determining extra‐pair male success. These results suggest that coloration plays a role in the formation of social pairs, but not mate choice for extra‐pair partners.